Transnational messages : experiences of Chinese and Mexican immigrants in American schools - Brittain, Carmina (New Americans (LFB Scholarly Publishing LLC), 2002)
Annotation Spurred by the observation that the exchange of information is one of the major resources available to immigrant students, Brittain (education, U. of California-Berkeley) investigates whether members of the two immigrant groups interact with other students from the same country and exchange information about their experiences in American schools that shaped their schooling experience. Her study provides insight into how perceptions of US schools are constructions among transnational human groups of co-nationals and how they reflect specific values or expectations that Chinese and Mexican immigrant children hold regarding American schooling. Annotation copyrighted by Book News, Inc., Portland, OR.